THE INFLUENCE OF FAMILY SUPPORT ON THE PREVENTION OF EARLY MARRIAGE IN DONOMULYO DISTRICT, MALANG REGENCY - Ayu Sherlita Sari; Sulistiyah (Journal of Public Health Science, 2026)
Early marriage, which occurs during adolescence before reaching the recommended age for marriage, remains a significant social issue in Indonesia because of its adverse effects on adolescents' health, education, and social well-being. Family support is considered one of the key factors influencing efforts to prevent early marriage. This study aimed to examine the effect of family support on the prevention of early marriage among adolescents in Donomulyo District, Malang Regency. A quantitative correlational study with a cross-sectional design was conducted involving 35 adolescents selected through total sampling. Data were collected using validated family support and early marriage prevention questionnaires and analyzed using simple linear regression with IBM SPSS Statistics. The findings indicated that both family support and early marriage prevention were predominantly at a moderate level. Regression analysis demonstrated a very strong positive relationship between family support and early marriage prevention (R = 0.995), with family support explaining 98.9% of the variance in early marriage prevention (R² = 0.989). The regression model was statistically significant (F = 2998.831, p < 0.001), and family support had a significant positive effect on early marriage prevention (β = 0.995; B = 0.991; t = 54.762; p < 0.001). These findings indicate that stronger family support is associated with greater adolescent readiness to delay marriage through improved awareness of education, reproductive health, and psychosocial maturity. Therefore, family-centered interventions that strengthen parental communication, emotional support, and reproductive health education should be prioritized as practical strategies to reduce the risk of early marriage among adolescents.